Low-cost corrosion-resistant alpha + beta double-phase titanium alloy and preparation method thereof

By using Fe elements instead of V elements in α+β biphasic titanium alloys, the problem of high cost of titanium alloys is solved, low-cost corrosion resistance is achieved, and the application range of titanium alloys is expanded.

CN119162490APending Publication Date: 2024-12-20HARBIN INST OF TECH

Patent Information

Application Number
CN202411468460.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing α+β biphasic titanium alloys have high costs, which is mainly due to the high price of V elements, which limits its wide application.

Method used

The Fe element is used instead of V element, and the Ti-6Al-xV-2Sn-0.5Cu-yFe alloy is prepared by adjusting the alloy composition and preparation process. The β-phase stability and solid solution strengthening effect of Fe element are used to reduce costs and improve costs. Corrosion resistance.

Benefits of technology

有效降低了钛合金的原材料成本,保持或提高其耐腐蚀性能,实现了钛合金的低成本批量生产和广泛应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162490A_ABST
    Figure CN119162490A_ABST
Patent Text Reader

Abstract

The invention discloses a low-cost corrosion-resistant alpha + beta double-phase titanium alloy and a preparation method thereof, and relates to the field of titanium alloy preparation. The method aims at solving the problem that an existing alpha + beta double-phase titanium alloy is high in cost. The expression of the alpha + beta double-phase titanium alloy is Ti-6Al-xV-2Sn-0.5 Cu-yFe. The method comprises the following steps: 1, weighing raw materials; 2, the raw materials are pretreated and placed in a vacuum arc furnace, meanwhile, titanium sponge is added into adjacent crucibles, a furnace door is closed, and after the vacuum arc furnace is vacuumized, inert gas is filled; 3, melting the sponge titanium in the adjacent crucibles by adopting an electric arc to absorb oxygen, smelting other raw materials, and starting electromagnetic stirring in the smelting process; and 4, after smelting is finished, cooling is conducted, and the alpha + beta double-phase titanium alloy is obtained. According to the titanium alloy with the components, the cost of raw materials can be greatly reduced, and batch production of the titanium alloy can be achieved conveniently. The method is used for preparing the corrosion-resistant alpha + beta double-phase titanium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of titanium alloy preparation, and in particular to a low-cost, corrosion-resistant α+β dual-phase titanium alloy and a preparation method thereof. Background Art

[0002] Titanium is abundant on earth and has the characteristics of high specific strength, corrosion resistance, heat resistance and wide operating temperature range. Since a passivation film with good stability and strong bonding ability will spontaneously form on the surface of titanium, titanium alloy has excellent corrosion resistance in highly corrosive environments such as marine atmosphere and seawater.

[0003] However, due to the high pursuit of titanium alloy composition and technology, although the corrosion resistance and mechanical properties of titanium alloy are improved. But at the same time, the raw material and preparation cost of titanium alloy are also increased, which makes the price of titanium alloy remain high, limiting its further application. At present, titanium alloy cannot be used on a large scale like traditional materials, and the biggest reason is the cost of materials. Once this problem is solved, titanium alloy can replace materials in many industries, and the amount of titanium alloy will also increase significantly. For this reason, it is of great significance to develop a low-cost titanium alloy.

[0004] The high cost of titanium alloys can be considered from the aspects of alloy raw materials, alloy preparation technology, etc. V element, as a β-stabilizing element of titanium alloy, is an indispensable element in α+β duplex titanium alloy. For example, the most classic α+β duplex titanium alloy (Ti-6Al-4V), V element is very expensive, so V element is the main reason for the high cost of this type of titanium alloy. Summary of the invention

[0005] The present invention aims to solve the problem of high cost of existing α+β dual-phase titanium alloys and provide a low-cost, corrosion-resistant α+β dual-phase titanium alloy and a preparation method thereof.

[0006] The present invention provides a low-cost, corrosion-resistant α+β dual-phase titanium alloy, which is expressed as Ti-6Al-xV-2Sn-0.5Cu-yFe, wherein x+y=6.5, x=0, 1.5, 3, 4.5 or 6;

[0007] The Ti-Al-xV-Sn-Cu-yFe alloy is made of the following raw materials in percentage by mass: 75% Ti, 6% Al, 0%-6% V, 2% Sn, 0.5% Cu, and 0.5%-6.5% Fe.

[0008] The present invention also provides a method for preparing the above-mentioned α+β dual-phase titanium alloy, comprising the following steps:

[0009] 1. Weigh the raw materials according to the mass percentage of each element: Ti 75%, Al 6%, V 0%-6%, Sn 2%, Cu 0.5% and Fe0.5%-6.5%;

[0010] 2. Pre-treat the raw materials, wrap the Fe powder with aluminum foil, put it into a water-cooled copper crucible, and place the water-cooled copper crucible in a vacuum arc furnace, then put Al particles, sponge Ti, V particles, Sn particles, Fe particles and Cu particles on the Fe powder in sequence, and add sponge titanium to the adjacent crucible at the same time, close the furnace door, evacuate the vacuum arc furnace, and fill it with inert gas;

[0011] 3. First, arc melting is used to melt the titanium sponge in the adjacent crucibles to absorb oxygen, and then the remaining raw materials are melted, and electromagnetic stirring is turned on during the melting process;

[0012] 4. After the smelting is completed, the alloy is cooled to obtain a cast Ti-6Al-xV-2Sn-0.5Cu-yFe alloy, which is an α+β dual-phase titanium alloy.

[0013] Furthermore, the purity of the raw materials in step 1 is above 99.95%.

[0014] Furthermore, in the raw materials described in step 1, the Ti element is sponge titanium, the Al element is Al particles, the V element is V particles, the Sn element is Sn particles, the Cu element is Cu particles, and the Fe element is Fe powder.

[0015] Furthermore, the melting is performed 5 times in step 3, and after each melting, the alloy ingot is turned 180° and then melted again.

[0016] Furthermore, in the first four of the five melting times in step three, the current is increased from 0A to 600A and maintained at 600A for 60-80s, the alloy ingot is melted by a high temperature arc, and then cooled and the current is reduced to 0A.

[0017] Furthermore, in the last smelting of the 5 smeltings in step 3, the current is increased from 0 A to 600 A, and maintained at 600 A for 60-80 s, the alloy ingot is melted by a high-temperature arc, cooled, the current is reduced from 600 A to 350 A, and then further reduced to 200 A at a rate of 50 A per 10 s, and then the current is reduced to 0 A.

[0018] Beneficial effects of the present invention:

[0019] The titanium alloy composition of the present invention adopts Ti-6Al-xV-2Sn-0.5Cu-yFe alloy, and replaces the β-stabilizing element V element in the α+β dual-phase titanium alloy with the β-stabilizing element Fe element, which can greatly reduce the cost. The current cost of the V element is 350 yuan per 100 grams, while the current cost of the Fe element is 4.5 yuan per 100 grams. Therefore, the cost of the V element is about 78 times the cost of the Fe element. Therefore, the titanium alloy of the composition of the present invention can greatly reduce the cost of raw materials, facilitate the mass production of the titanium alloy, and expand the application of the new α+β dual-phase titanium alloy in practice.

[0020] Since the chemical properties of Fe element are relatively active, it is easy to react chemically with the surrounding medium to generate corrosion products. Therefore, it is generally believed that adding Fe element as an alloying element to α+β dual-phase titanium alloy will reduce the corrosion resistance of Ti alloy. The present invention has found that since Fe element is one of the strongest β-phase stabilizing elements for Ti alloy, it can significantly reduce the α / β transition temperature and increase the content of β phase. After the Fe element is added, the Fe atoms mainly enter the β phase in a solid solution manner and will not precipitate a second phase. Since Ti alloy is mainly composed of α phase and β phase, and compared with α phase, β phase has better corrosion resistance. Therefore, Fe element will improve the corrosion resistance of Ti alloy by regulating the phase composition and phase content in Ti alloy and solid solution strengthening, and will not deteriorate. This is different from the mechanism of poor corrosion resistance of Fe element itself. The present invention overcomes technical prejudice.

[0021] In the present invention, the Fe element and the V element are both β-phase stabilizing elements for titanium alloys. The role of the Fe element in the α+β duplex titanium alloy is similar to that of the V element in the α+β duplex titanium alloy. Therefore, using the Fe element to replace the V element has the least effect on the various properties of the original α+β duplex titanium alloy.

[0022] The present invention applies electromagnetic stirring during the smelting process. Since the Fe element in the titanium alloy will cause β segregation, that is, form β spots, the Fe element will be enriched in the β phase in large quantities, thereby adversely affecting various properties of the alloy. When electromagnetic stirring is used to stir the alloy melt in the water-cooled copper crucible, it is beneficial to the diffusion of Fe atoms, thereby inhibiting the formation of β spots and improving the performance of the Ti alloy.

[0023] The performance of a new type of α+β titanium alloy with low cost and high corrosion resistance prepared by the method of the present invention can be further improved after heat treatment and deformation and other processes. The present invention is a new type of α+β titanium alloy with low cost and high corrosion resistance with great potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1The corrosion potential and corrosion current density of the Ti-Al-xV-Sn-Cu-yFe dual-phase α+β titanium alloy prepared in Examples 1 to 5.

[0025] Figure 2 A bar chart showing the costs required for preparing the Ti-Al-xV-Sn-Cu-yFe dual-phase α+β titanium alloy raw materials obtained in Examples 1 to 5. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0027] Specific implementation method 1: The α+β dual-phase titanium alloy of this implementation method is expressed as Ti-6Al-xV-2Sn-0.5Cu-yFe, wherein x+y=6.5, x=0, 1.5, 3, 4.5 or 6.

[0028] Specific embodiment 2: The preparation method of the α+β dual-phase titanium alloy in this embodiment includes the following steps:

[0029] 1. Weigh the raw materials according to the mass percentage of each element: Ti 75%, Al 6%, V 0%-6%, Sn 2%, Cu 0.5% and Fe0.5%-6.5%;

[0030] 2. Pre-treat the raw materials, wrap the Fe powder with aluminum foil, put it into a water-cooled copper crucible, and place the water-cooled copper crucible in a vacuum arc furnace, then put Al particles, sponge Ti, V particles, Sn particles, Fe particles and Cu particles on the Fe powder in sequence, and add sponge titanium to the adjacent crucible at the same time, close the furnace door, evacuate the vacuum arc furnace, and fill it with inert gas;

[0031] 3. First, arc melting is used to melt the titanium sponge in the adjacent crucibles to absorb oxygen, and then the remaining raw materials are melted, and electromagnetic stirring is turned on during the melting process;

[0032] 4. After the smelting is completed, the alloy is cooled to obtain a cast Ti-6Al-xV-2Sn-0.5Cu-yFe alloy, which is an α+β dual-phase titanium alloy.

[0033] In this embodiment, a large amount of titanium sponge is placed in the groove of an idle water-cooled copper crucible, and before the formal melting of the Ti alloy, an arc gun is used to melt the titanium sponge placed in the water-cooled copper crucible at high temperature. During the melting process of the titanium sponge, a large amount of oxygen is absorbed, further improving the vacuum degree in the vacuum arc furnace. This makes the formally melted Ti alloy less contaminated by oxygen, reducing the influence of oxygen on the performance of the titanium alloy.

[0034] The preparation method of this embodiment adopts vacuum non-consumable arc melting technology, wherein the arc melting adopts a water-cooled copper crucible. The water-cooled copper crucible has low cost, simple process, short preparation cycle and is easy to implement.

[0035] Specific implementation method 3: In step 1 of this implementation method, the purity of the raw materials is above 99.95%. Other parameters and steps are the same as those of specific implementation method 2.

[0036] Specific implementation method 4: In step 1 of this implementation method, the raw materials of Ti are sponge titanium, Al are Al particles, V are V particles, Sn are Sn particles, Cu are Cu particles, and Fe are Fe powder. Other parameters and steps are the same as those of specific implementation method 2 or 3.

[0037] Specific implementation method 5: The number of smelting in step 3 of this implementation method is 5 times, and after each smelting, the alloy ingot is turned 180 degrees and then smelted again. Other parameters and steps are the same as those of specific implementation methods 2 to 4.

[0038] Specific implementation method 6: In the first four smeltings of the five smeltings in step 3 of this implementation method, the current is increased from 0 A to 600 A and maintained at 600 A for 60-80 seconds to melt the alloy ingot using a high temperature arc, and then cooled to reduce the current to 0 A. Other parameters and steps are the same as those in specific implementation method 5.

[0039] In this embodiment, the temperature is maintained at 600A for 60-80s, and the alloy melted out has more uniform composition and better corrosion resistance.

[0040] Specific embodiment 7: In the last smelting of the five smeltings in step 3 of this embodiment, the current is increased from 0 A to 600 A, and maintained at 600 A for 60-80 seconds, the alloy ingot is melted by a high-temperature arc, cooled, the current is reduced from 600 A to 350 A, and then continued to be reduced to 200 A at a rate of 50 A per 10 seconds, and then the current is reduced to 0 A. Other parameters and steps are the same as those in specific embodiments 5 or 6.

[0041] The cooling method adopted in the last smelting of this embodiment and the control of the cooling rate during the final solidification can effectively control the microsegregation in the alloy, make the alloy composition more uniform, reduce the galvanic corrosion between different phases in the alloy, and further improve the corrosion resistance of the alloy.

[0042] The embodiments of the present invention are described in detail below. The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation schemes and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0043] Embodiment 1:

[0044] The α+β dual-phase titanium alloy of this embodiment is Ti-6Al-6V-2Sn-0.5Cu-0.5Fe alloy.

[0045] The composition is as follows in mass percentage: Ti: 75%, Al: 6%, V: 6%, Sn: 2%, Cu: 0.5%, and Fe: 0.5%.

[0046] The preparation method of the α+β dual-phase titanium alloy in this embodiment comprises the following steps:

[0047] 1. Weigh the raw materials according to the mass percentage of each element: Ti 75%, Al 6%, V 6%, Sn 2%, Cu 0.5% and Fe0.5%. The Ti single substance is sponge titanium with a purity of more than 99.9%, and the Al single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The V single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The Sn single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The Cu single substance is irregular particles of 2-4 mm with a purity of more than 99.9%, and the Fe single substance is Fe powder with a purity of more than 99.9%. It is necessary to weigh additional sponge titanium and put it into the vacuum arc furnace to absorb oxygen and increase the vacuum degree of the vacuum arc furnace.

[0048] 2. Pre-treat the surface of raw materials to prevent the introduction of impurities during alloy smelting. First, use 60# sandpaper to polish the surface of titanium sponge, Al particles, V particles, Sn particles and Cu particles. The Fe element in the raw materials is in powder form, so no pre-treatment is required.

[0049] The polished titanium sponge, Al particles, V particles, Sn particles and Cu particles are placed in deionized water for ultrasonic cleaning. The first cleaning time is 5 minutes, the power and frequency are 60W and 24kHz respectively, and the raw materials cleaned for the first time are air-dried. Then the raw materials after the first cleaning are cleaned for the second time, and the raw materials are placed in acetone solution for ultrasonic cleaning. The second cleaning time is 7 minutes, and the power and frequency are 80W and 28kHz respectively. The raw materials after the second acetone wash are air-dried with hot air. Finally, the third ultrasonic cleaning is carried out, and the raw materials after the second air drying are placed in anhydrous ethanol for ultrasonic cleaning. The third cleaning time is 10 minutes, and the power and frequency are 100W and 30kHz respectively.

[0050] 3. Wrap the Fe powder with Al foil and put it into a water-cooled copper crucible, and then place the water-cooled copper crucible in a vacuum arc furnace. Then, Al particles, sponge Ti, V particles, Sn particles, Fe particles and Cu particles are placed on the Fe powder in sequence. At the same time, an excess of sponge titanium is placed in the groove of another adjacent crucible, and the furnace door is closed.

[0051] 4. Pump the vacuum in the furnace chamber to 5×10 -3 Pa, and open the argon valve to fill the vacuum arc furnace with high-purity argon gas so that the pressure display attached to the furnace body reaches -0.05MPa.

[0052] 5. First, turn on the switch of the arc gun, aim the arc gun at the sponge titanium in the adjacent crucible, control the melting current to slowly increase from 0A to 600A, and ensure that the flow rate of the circulating cooling water is 3m / s, melt the excess sponge titanium, so as to absorb the residual oxygen in the vacuum arc furnace and increase the vacuum degree in the arc furnace.

[0053] 6. Then the remaining raw materials are melted. Electromagnetic stirring needs to be turned on during the entire smelting process. In order to ensure that the composition of the smelted alloy ingot is uniform and there is less segregation, the smelting is repeated 5 times. After each smelting, a robot is used to turn the alloy ingot 180° before smelting again.

[0054] The first four smeltings were to slowly increase the current from 0A to 600A and maintain it at 600A for 60s, using a high-temperature arc to melt the alloy ingot, then cool it and reduce the current to 0A.

[0055] In the last smelting, the current was increased from 0A to 600A and maintained at 600A for 60s, and the alloy ingot was melted by a high-temperature arc. After cooling, the current was reduced from 600A to 350A, and then continued to decrease to 200A at a rate of 50A every 10s, and then slowly reduced to 0A.

[0056] 7. After the smelting is completed, open the air valve, fill the furnace with air and open the furnace door. After the temperature in the furnace cools down, take out the alloy ingot, and the smelting is completed to obtain Ti-6Al-6V-2Sn-0.5Cu-0.5Fe alloy.

[0057] Embodiment 2:

[0058] The α+β dual-phase titanium alloy of this embodiment is Ti-6Al-6V-2Sn-0.5Cu-0.5Fe alloy.

[0059] The composition is as follows by mass percentage: Ti: 75%, Al: 6%, V: 4.5%, Sn: 2%, Cu: 0.5%, and Fe: 2%.

[0060] The preparation method of the α+β dual-phase titanium alloy in this embodiment comprises the following steps:

[0061] 1. Weigh the raw materials according to the mass percentage of each element: Ti 75%, Al 6%, V 4.5%, Sn 2%, Cu 0.5% and Fe2%. The Ti single substance is sponge titanium with a purity of more than 99.9%, and the Al single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The V single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The Sn single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The Cu single substance is irregular particles of 2-4 mm with a purity of more than 99.9%, and the Fe single substance is Fe powder with a purity of more than 99.9%. It is necessary to weigh additional sponge titanium and put it into the vacuum arc furnace to absorb oxygen and increase the vacuum degree in the vacuum arc furnace.

[0062] 2. Pre-treat the surface of raw materials to prevent the introduction of impurities during alloy smelting. First, use 60# sandpaper to polish the surface of titanium sponge, Al particles, V particles, Sn particles and Cu particles. The Fe element in the raw materials is in powder form, so no pre-treatment is required.

[0063] The polished titanium sponge, Al particles, V particles, Sn particles and Cu particles are placed in deionized water for ultrasonic cleaning. The first cleaning time is 5 minutes, the power and frequency are 60W and 24kHz respectively, and the raw materials cleaned for the first time are air-dried. Then the raw materials after the first cleaning are cleaned for the second time, and the raw materials are placed in acetone solution for ultrasonic cleaning. The second cleaning time is 7 minutes, and the power and frequency are 80W and 28kHz respectively. The raw materials after the second acetone wash are air-dried with hot air. Finally, the third ultrasonic cleaning is carried out, and the raw materials after the second air drying are placed in anhydrous ethanol for ultrasonic cleaning. The third cleaning time is 10 minutes, and the power and frequency are 100W and 30kHz respectively.

[0064] 3. Wrap the Fe powder with Al foil and put it into a water-cooled copper crucible, and then place the water-cooled copper crucible in a vacuum arc furnace. Then, Al particles, sponge Ti, V particles, Sn particles, Fe particles and Cu particles are placed on the Fe powder in sequence. At the same time, an excess of sponge titanium is placed in the groove of another adjacent crucible, and the furnace door is closed.

[0065] 4. Pump the vacuum in the furnace chamber to 5×10 -3 Pa, and open the argon valve to fill the vacuum arc furnace with high-purity argon gas so that the pressure display attached to the furnace body reaches -0.05MPa.

[0066] 5. First, turn on the switch of the arc gun, aim the arc gun at the sponge titanium in the adjacent crucible, control the melting current to slowly increase from 0A to 600A, and ensure that the flow rate of the circulating cooling water is 3m / s, melt the excess sponge titanium, so as to absorb the residual oxygen in the vacuum arc furnace and increase the vacuum degree in the arc furnace.

[0067] 6. Then the remaining raw materials are melted. Electromagnetic stirring needs to be turned on during the entire smelting process. In order to ensure that the composition of the smelted alloy ingot is uniform and there is less segregation, the smelting is repeated 5 times. After each smelting, a robot is used to turn the alloy ingot 180° before smelting again.

[0068] The first four smeltings were to slowly increase the current from 0A to 600A and maintain it at 600A for 60s, using a high-temperature arc to melt the alloy ingot, then cool it and reduce the current to 0A.

[0069] In the last smelting, the current was increased from 0A to 600A and maintained at 600A for 60s, and the alloy ingot was melted by a high-temperature arc. After cooling, the current was reduced from 600A to 350A, and then continued to decrease to 200A at a rate of 50A every 10s, and then slowly reduced to 0A.

[0070] 7. After the smelting is completed, open the air valve, fill the furnace with air and open the furnace door. After the temperature in the furnace cools down, take out the alloy ingot, and the smelting is completed to obtain Ti-6Al-4.5V-2Sn-0.5Cu-2Fe alloy.

[0071] Embodiment 3:

[0072] The α+β dual-phase titanium alloy of this embodiment is Ti-6Al-6V-2Sn-0.5Cu-0.5Fe alloy.

[0073] The composition is as follows in mass percentage: Ti: 75%, Al: 6%, V: 3%, Sn: 2%, Cu: 0.5%, and Fe: 3.5%.

[0074] The preparation method of the α+β dual-phase titanium alloy in this embodiment comprises the following steps:

[0075] 1. Weigh the raw materials according to the mass percentage of each element: Ti 75%, Al 6%, V 3%, Sn 2%, Cu 0.5% and Fe3.5%. The Ti single substance is sponge titanium with a purity of more than 99.9%, and the Al single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The V single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The Sn single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The Cu single substance is irregular particles of 2-4 mm with a purity of more than 99.9%, and the Fe single substance is Fe powder with a purity of more than 99.9%. It is necessary to weigh additional sponge titanium and put it into the vacuum arc furnace to absorb oxygen and increase the vacuum degree in the vacuum arc furnace.

[0076] 2. Pre-treat the surface of raw materials to prevent the introduction of impurities during alloy smelting. First, use 60# sandpaper to polish the surface of titanium sponge, Al particles, V particles, Sn particles and Cu particles. The Fe element in the raw materials is in powder form, so no pre-treatment is required.

[0077] The polished titanium sponge, Al particles, V particles, Sn particles and Cu particles are placed in deionized water for ultrasonic cleaning. The first cleaning time is 5 minutes, the power and frequency are 60W and 24kHz respectively, and the raw materials cleaned for the first time are air-dried. Then the raw materials after the first cleaning are cleaned for the second time, and the raw materials are placed in acetone solution for ultrasonic cleaning. The second cleaning time is 7 minutes, and the power and frequency are 80W and 28kHz respectively. The raw materials after the second acetone wash are air-dried with hot air. Finally, the third ultrasonic cleaning is carried out, and the raw materials after the second air drying are placed in anhydrous ethanol for ultrasonic cleaning. The third cleaning time is 10 minutes, and the power and frequency are 100W and 30kHz respectively.

[0078] 3. Wrap the Fe powder with Al foil and put it into a water-cooled copper crucible, and then place the water-cooled copper crucible in a vacuum arc furnace. Then, Al particles, sponge Ti, V particles, Sn particles, Fe particles and Cu particles are placed on the Fe powder in sequence. At the same time, an excess of sponge titanium is placed in the groove of another adjacent crucible, and the furnace door is closed.

[0079] 4. Pump the vacuum in the furnace chamber to 5×10 -3 Pa, and open the argon valve to fill the vacuum arc furnace with high-purity argon gas so that the pressure display attached to the furnace body reaches -0.05MPa.

[0080] 5. First, turn on the switch of the arc gun, aim the arc gun at the sponge titanium in the adjacent crucible, control the melting current to slowly increase from 0A to 600A, and ensure that the flow rate of the circulating cooling water is 3m / s, melt the excess sponge titanium, so as to absorb the residual oxygen in the vacuum arc furnace and increase the vacuum degree in the arc furnace.

[0081] 6. Then the remaining raw materials are melted. Electromagnetic stirring needs to be turned on during the entire smelting process. In order to ensure that the composition of the smelted alloy ingot is uniform and there is less segregation, the smelting is repeated 5 times. After each smelting, a robot is used to turn the alloy ingot 180° before smelting again.

[0082] The first four smeltings were to slowly increase the current from 0A to 600A and maintain it at 600A for 60s, using a high-temperature arc to melt the alloy ingot, then cool it and reduce the current to 0A.

[0083] In the last smelting, the current was increased from 0A to 600A and maintained at 600A for 60s, and the alloy ingot was melted by a high-temperature arc. After cooling, the current was reduced from 600A to 350A, and then continued to decrease to 200A at a rate of 50A every 10s, and then slowly reduced to 0A.

[0084] 7. After the smelting is completed, open the air valve, fill the furnace with air and open the furnace door. After the temperature in the furnace cools down, take out the alloy ingot, and the smelting is completed to obtain Ti-6Al-3V-2Sn-0.5Cu-3.5Fe alloy.

[0085] Embodiment 4:

[0086] The α+β dual-phase titanium alloy of this embodiment is Ti-6Al-6V-2Sn-0.5Cu-0.5Fe alloy.

[0087] The composition is as follows by mass percentage: Ti is 75%, Al is 6%, V is 1.5%, Sn is 2%, Cu is 0.5%, and Fe is 5%.

[0088] The preparation method of the α+β dual-phase titanium alloy in this embodiment comprises the following steps:

[0089] 1. Weigh the raw materials according to the mass percentage of each element: Ti 75%, Al 6%, V 1.5%, Sn 2%, Cu 0.5% and Fe5%. The Ti single substance is sponge titanium with a purity of more than 99.9%, and the Al single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The V single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The Sn single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The Cu single substance is irregular particles of 2-4 mm with a purity of more than 99.9%, and the Fe single substance is Fe powder with a purity of more than 99.9%. It is necessary to weigh additional sponge titanium and put it into the vacuum arc furnace to absorb oxygen and increase the vacuum degree in the vacuum arc furnace.

[0090] 2. Pre-treat the surface of raw materials to prevent the introduction of impurities during alloy smelting. First, use 60# sandpaper to polish the surface of titanium sponge, Al particles, V particles, Sn particles and Cu particles. The Fe element in the raw materials is in powder form, so no pre-treatment is required.

[0091] The polished titanium sponge, Al particles, V particles, Sn particles and Cu particles are placed in deionized water for ultrasonic cleaning. The first cleaning time is 5 minutes, the power and frequency are 60W and 24kHz respectively, and the raw materials cleaned for the first time are air-dried. Then the raw materials after the first cleaning are cleaned for the second time, and the raw materials are placed in acetone solution for ultrasonic cleaning. The second cleaning time is 7 minutes, and the power and frequency are 80W and 28kHz respectively. The raw materials after the second acetone wash are air-dried with hot air. Finally, the third ultrasonic cleaning is carried out, and the raw materials after the second air drying are placed in anhydrous ethanol for ultrasonic cleaning. The third cleaning time is 10 minutes, and the power and frequency are 100W and 30kHz respectively.

[0092] 3. Wrap the Fe powder with Al foil and put it into a water-cooled copper crucible, and then place the water-cooled copper crucible in a vacuum arc furnace. Then, Al particles, sponge Ti, V particles, Sn particles, Fe particles and Cu particles are placed on the Fe powder in sequence. At the same time, an excess of sponge titanium is placed in the groove of another adjacent crucible, and the furnace door is closed.

[0093] 4. Pump the vacuum in the furnace chamber to 5×10 -3 Pa, and open the argon valve to fill the vacuum arc furnace with high-purity argon gas so that the pressure display attached to the furnace body reaches -0.05MPa.

[0094] 5. First, turn on the switch of the arc gun, aim the arc gun at the sponge titanium in the adjacent crucible, control the melting current to slowly increase from 0A to 600A, and ensure that the flow rate of the circulating cooling water is 3m / s, melt the excess sponge titanium, so as to absorb the residual oxygen in the vacuum arc furnace and increase the vacuum degree in the arc furnace.

[0095] 6. Then the remaining raw materials are melted. Electromagnetic stirring needs to be turned on during the entire smelting process. In order to ensure that the composition of the smelted alloy ingot is uniform and there is less segregation, the smelting is repeated 5 times. After each smelting, a robot is used to turn the alloy ingot 180° before smelting again.

[0096] The first four smeltings were to slowly increase the current from 0A to 600A and maintain it at 600A for 60s, using a high-temperature arc to melt the alloy ingot, then cool it and reduce the current to 0A.

[0097] In the last smelting, the current was increased from 0A to 600A and maintained at 600A for 60s, and the alloy ingot was melted by a high-temperature arc. After cooling, the current was reduced from 600A to 350A, and then continued to decrease to 200A at a rate of 50A every 10s, and then slowly reduced to 0A.

[0098] 7. After the smelting is completed, open the air valve, fill the furnace with air and open the furnace door. After the temperature in the furnace cools down, take out the alloy ingot, and the smelting is completed to obtain Ti-6Al-1.5V-2Sn-0.5Cu-5Fe alloy.

[0099] Embodiment 5:

[0100] The α+β dual-phase titanium alloy of this embodiment is Ti-6Al-6V-2Sn-0.5Cu-0.5Fe alloy.

[0101] The composition is as follows by mass percentage: Ti: 75%, Al: 6%, Sn: 2%, Cu: 0.5%, and Fe: 6.5%.

[0102] The preparation method of the α+β dual-phase titanium alloy in this embodiment comprises the following steps:

[0103] 1. Weigh the raw materials according to the mass percentage of each element: Ti 75%, Al 6%, Sn 2%, Cu 0.5% and Fe 6.5%. The Ti single substance is sponge titanium with a purity of more than 99.9%, and the Al single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The Sn single substance is irregular particles of 2-4 mm with a purity of more than 99.9%. The Cu single substance is irregular particles of 2-4 mm with a purity of more than 99.9%, and the Fe single substance is Fe powder with a purity of more than 99.9%. It is necessary to weigh additional sponge titanium and put it into the vacuum arc furnace to absorb oxygen and increase the vacuum degree in the vacuum arc furnace.

[0104] 2. Pre-treat the surface of raw materials to prevent the introduction of impurities during alloy smelting. First, use 60# sandpaper to polish the surface of titanium sponge, Al particles, Sn particles and Cu particles. The Fe element in the raw materials is in powder form, so no pre-treatment is required.

[0105] The polished titanium sponge, Al particles, Sn particles and Cu particles are placed in deionized water for ultrasonic cleaning. The first cleaning time is 5 minutes, the power and frequency are 60W and 24kHz respectively, and the raw materials cleaned for the first time are air-dried. Then the raw materials after the first cleaning are cleaned for the second time, and the raw materials are placed in acetone solution for ultrasonic cleaning. The second cleaning time is 7 minutes, and the power and frequency are 80W and 28kHz respectively. The raw materials after the second acetone wash are air-dried with hot air. Finally, the third ultrasonic cleaning is carried out, and the raw materials after the second air drying are placed in anhydrous ethanol for ultrasonic cleaning. The third cleaning time is 10 minutes, and the power and frequency are 100W and 30kHz respectively.

[0106] 3. Wrap the Fe powder with Al foil and put it into a water-cooled copper crucible, and then place the water-cooled copper crucible in a vacuum arc furnace. Then, Al particles, sponge Ti, Sn particles, Fe particles and Cu particles are placed on the Fe powder in sequence. At the same time, an excess of sponge titanium is placed in the groove of another adjacent crucible, and the furnace door is closed.

[0107] 4. Pump the vacuum in the furnace chamber to 5×10 -3 Pa, and open the argon valve to fill the vacuum arc furnace with high-purity argon gas so that the pressure display attached to the furnace body reaches -0.05MPa.

[0108] 5. First, turn on the switch of the arc gun, aim the arc gun at the sponge titanium in the adjacent crucible, control the melting current to slowly increase from 0A to 600A, and ensure that the flow rate of the circulating cooling water is 3m / s, melt the excess sponge titanium, so as to absorb the residual oxygen in the vacuum arc furnace and increase the vacuum degree in the arc furnace.

[0109] 6. Then the remaining raw materials are melted. Electromagnetic stirring needs to be turned on during the entire smelting process. In order to ensure that the composition of the smelted alloy ingot is uniform and there is less segregation, the smelting is repeated 5 times. After each smelting, a robot is used to turn the alloy ingot 180° before smelting again.

[0110] The first four smeltings were to slowly increase the current from 0A to 600A and maintain it at 600A for 60s, using a high-temperature arc to melt the alloy ingot, then cool it and reduce the current to 0A.

[0111] In the last smelting, the current was increased from 0A to 600A and maintained at 600A for 60s, and the alloy ingot was melted by a high-temperature arc. After cooling, the current was reduced from 600A to 350A, and then continued to decrease to 200A at a rate of 50A every 10s, and then slowly reduced to 0A.

[0112] 7. After the smelting is completed, open the air valve, fill the furnace with air and open the furnace door. After the temperature in the furnace cools down, take out the alloy ingot, and the smelting is completed to obtain Ti-6Al-2Sn-0.5Cu-6.5Fe alloy.

[0113] The corrosion potential and corrosion current of the α+β dual-phase titanium alloy Ti-Al-xV-Sn-Cu-yFe prepared in Examples 1 to 5 in 5M HCl are as follows: Figure 1 shown.

[0114] The present invention adopts electrochemical experiment, uses the titanium alloy of various compositions in the above embodiment as working electrode, and exposes 1cm 2 The working area was measured in a 5 mol / L HCl solution with a platinum electrode as the counter electrode and a saturated calomel electrode as the reference electrode. The Tafel curve was fitted according to the cathode curve to calculate the corrosion current and corrosion potential. From the perspective of corrosion kinetics, as the Fe content in the alloy continues to increase, the value of the corrosion current continues to increase. This shows that the use of Fe elements to replace the V element in the α+β duplex titanium alloy increases the corrosion rate of the alloy, but when the Fe content reaches 3.5% by mass, the corrosion current of the alloy increases to the maximum, and then does not change much. Moreover, as more and more Fe elements replace V elements, the corrosion potential of the alloy continues to increase, which shows that the tendency to corrosion is getting smaller and smaller, and the thermal stability of the alloy is getting higher and higher.

[0115] In summary, as more and more Fe elements replace V elements in α+β duplex titanium alloy, from the perspective of corrosion kinetics, the corrosion current density of the alloy gradually increases. This shows that the corrosion rate of the alloy in 5mol / L HCl solution is gradually accelerating. However, from the perspective of corrosion thermodynamics, as more and more V elements replace Fe elements, the corrosion potential of the alloy gradually increases, which shows that the corrosion thermodynamics is becoming more and more stable, and the corrosion tendency of the alloy in 5mol / L HCl solution is also getting smaller and smaller.

[0116] The raw material cost of the α+β dual-phase titanium alloy prepared in Examples 1 to 5 is as follows: Figure 2 As shown. Figure 2 It can be seen that as more and more cheap Fe elements replace the expensive V elements in the alloy composition. The cost of titanium alloy continues to decrease. At present, the price of V element is about 3,500 yuan per kilogram. The price of Fe element is about 45 yuan per kilogram. Therefore, the raw material cost of smelting Ti-6Al-6V-2Sn-0.5Cu-0.5Fe alloy is 300.33 yuan. The raw material cost of smelting Ti-6Al-2Sn-0.5Cu-6.5Fe alloy is 93.35 yuan. The cost has been reduced by 68.92%. Although from the perspective of corrosion kinetics, the corrosion rate increases slightly after a large amount of Fe elements replace V elements. However, from the perspective of corrosion thermodynamics, the corrosion potential increases and the tendency of corrosion decreases after a large amount of Fe elements replace V elements. Therefore, the use of Fe elements to replace V elements will greatly reduce the cost of the duplex α+β titanium alloy, weaken the corrosion tendency, and slightly increase the corrosion rate. It is a new type of low-cost corrosion-resistant duplex α+β titanium alloy.

Claims

1. A low-cost, corrosion-resistant α+β dual-phase titanium alloy, characterized in that: The expression of the α+β dual-phase titanium alloy is Ti-6Al-xV-2Sn-0.5Cu-yFe, wherein x+y=6.5, x=0, 1.5, 3, 4.5 or 6.

2. The method for preparing a low-cost, corrosion-resistant α+β dual-phase titanium alloy according to claim 1, characterized in that: The method comprises the following steps:

1. Weigh the raw materials according to the mass percentage of each element: Ti 75%, Al 6%, V 0%-6%, Sn 2%, Cu 0.5% and Fe0.5%-6.5%; 2. Pre-treat the raw materials, wrap the Fe powder with aluminum foil, put it into a water-cooled copper crucible, and place the water-cooled copper crucible in a vacuum arc furnace, then put Al particles, sponge Ti, V particles, Sn particles, Fe particles and Cu particles on the Fe powder in sequence, and add sponge titanium to the adjacent crucible at the same time, close the furnace door, evacuate the vacuum arc furnace, and fill it with inert gas; 3. First, arc melting is used to melt the titanium sponge in the adjacent crucibles to absorb oxygen, and then the remaining raw materials are melted, and electromagnetic stirring is turned on during the melting process; 4. After the smelting is completed, the alloy is cooled to obtain a cast Ti-6Al-xV-2Sn-0.5Cu-yFe alloy, which is an α+β dual-phase titanium alloy.

3. The method for preparing a low-cost, corrosion-resistant α+β dual-phase titanium alloy according to claim 2, characterized in that: The purity of the raw materials in step 1 is above 99.95%.

4. A method for preparing a low-cost, corrosion-resistant α+β dual-phase titanium alloy according to claim 2 or 3, characterized in that: In the raw materials of step 1, the Ti single substance is sponge titanium, the Al single substance is Al particles, the V single substance is V particles, the Sn single substance is Sn particles, the Cu single substance is Cu particles, and the Fe single substance is Fe powder.

5. The method for preparing a low-cost, corrosion-resistant α+β dual-phase titanium alloy according to claim 4, characterized in that: The number of smelting in step 3 is 5 times. After each smelting, the alloy ingot is turned 180° and then smelted again.

6. The method for preparing a low-cost, corrosion-resistant α+β dual-phase titanium alloy according to claim 5, characterized in that: Step 3: For the first four of the five melting times, the current is increased from 0A to 600A and maintained at 600A for 60-80s, the alloy ingot is melted by a high temperature arc, and then cooled and the current is reduced to 0A.

7. A method for preparing a low-cost, corrosion-resistant α+β dual-phase titanium alloy according to claim 5 or 6, characterized in that: Step 3: The last smelting of the 5 smeltings is to increase the current from 0A to 600A and maintain it at 600A for 60-80s, melt the alloy ingot by high-temperature arc, cool it, reduce the current from 600A to 350A, and then continue to reduce it to 200A at a rate of 50A every 10s, and then reduce the current to 0A.

Citation Information

Patent Citations

  • High-temperature titanium alloy applicable to use at temperature of 650 DEG C and preparation method thereof

    CN104745872A

  • Low-cost and high-performance titanium alloy and preparation method thereof

    CN104831122A

  • Low-cost titanium alloy and preparation method thereof

    CN106319286A

  • Ti-Al-Nb-Zr-Mo corrosion-resistant titanium alloy and preparation method thereof

    CN112176219A

  • Low-cost titanium alloy preparation method

    CN112813300A

Cited By

  • A low cost high strength two-phase titanium alloy and method of making same

    CN120174232B